Fundamentals of structural mechanics - Hjelmstad, Keith D. (Prentice-Hall, 1997)
It provides a modern introduction to structural mechanics weaving a thorough treatment of basic continuum mechanics through the theories of beams and static stability theory. The book provides a solid prerequisite to the study of the finite element method and is suited for graduate and advanced undergraduate students in civil and mechanical engineering.